Influence of eccentric loading and range of motion on enhancement associated with the stretch shortening cycle in various vertical jumps - Moran, K. A.; Wallace, E. W. (2001)
In direct contrast to isolated muscle studies, the use of a significant and greater magnitude of eccentric loading in vertical jumps [Depth jump (DJ) versus countermovement jump (CMJ)] does not result in a significant increase in jump height (Voigt et al., 1995) and may in fact result in a significant decrease (Bobbert et al., 1987). This discrepancy may be in part due to a lack of experimental control in joint range of motion employed in previous studies. To determine if an increase in eccentric loading enhances jump height and joint work done when range of motion is experimentally matched across jumps. Methods and procedures Seventeen male volleyball players performed three variations of the vertical jump: Static Jump (SJ), CMJ and DJ from a drop height of 30cm (DJ30). Knee joint range of motion (70° and 90° of flexion) and Trunk action (erect) were experimentally controlled. Sagittal plane kinematics and reaction forces were simultaneously sampled. Jump height was calculated from kinematic data and work done was calculated using Newtonian mechanics. The average of 12 trials for each subject were used in a two way repeated measures ANOVA. From 70° of knee flexion, significantly greater jump heights were produced with increases in eccentric loading [DJ30 > CMJ > SJ]. From 90° of knee flexion, jump height was significantly greater in both the DJ30 and the CMJ than the SJ [(DJ30, CMJ) > SJ]. The enhancements in jump height were significantly greater across all jump conditions when using 70° in comparison to 90° of knee flexion, with the exception of the comparison of the CMJ to the SJ. Hip work done was significantly greater with increases in eccentric loading [DJ30 > CMJ > SJ] using both 90° and 70° of Knee flexion. Knee and ankle joint work done followed the same trend when using 70° of Knee flexion, but no differences were apparent when using 90° of flexion. In line with studies on isolated muscles, when a small range of motion is employed increases in eccentric loading (up to a drop height of 30cm) enhance performance. This enhancement is significantly greater when a smaller range of motion is employed. The contribution of the three joints to the enhancement in jump height varied across Jump and Knee conditions.